Facets of certainty: A critique of the development of a fundamental cartesian notion - Sami, Muhammad (AUC Knowledge Fountain, 2018)
Descartes is usually seen as a thinker who does not employ and preconceived principles in his system without establishing them first through his method. Through an analysis of the development of his notion of certain knowledge, I highlight his reliance in the development of such a principles on principles that he borrows from scholastic philosophy. These principles are unjustified and unjustifiable through his method. I argue that, on Descartes's own terms, this notion should fail. Indeed, this is what happens over the course of the one hundred and fifty years following the publication of Descartes's Meditations. I provide the conclusion that Descartes ends up with a notion of certain knowledge of truth that is psychological rather than ontological and ask whether the loss of an ontological commitment to truth is related to his unjustified rejection of substantial forms.